Experimental And Numerical Studies Of Structural Behavior Of Segmental Arch Beam - Asaad hamdan maryoosh (Genius Journals, 2026)
This investigation aims to study the structural behavior of reinforced concrete arches. To achieve this aim; the experimental and numerical analyses were conducted. Five reinforced concrete arches prepared in the lab and tested under static loading at midspan of the arches. The cross-section of these arches was T-section. The parametric studies were also accomplished to emulate the influence of differences in segmental configuration, number of segments and the types of the joints on the real structural response of reinforced concrete arches. Also, the numerical analysis was carried out by using a commercial finite element program that is ANSYS v.18.2. The numerical results compared with the experimental measurements. It is found that the peak percentage difference between numerical and experimental results not greater than 16%, and hence, good agreement achieved between them. The main results of this investigation that is the segmental configuration of concrete has active effects on the strength capacity of the reinforced concrete arch and on the deflection. Additionally, the ultimate load of the arches that are consist of the joints decreased by 23% to 57% compared with the reference arch.
Keywords: Reinforced Concrete Arches; segmental configuration; types of joint